ANALISIS GAYA BAHASA DALAM NOVEL 3726 MDPL KARYA NURWINA SARI - Krisdayanti; Idawati; Aswati Asri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Language Style in the Novel 3726 MDPL by Nurwina Sari. This study aims to describe the language styles found in the novel 3726 MDPL by Nurwina Sari. This research employed a descriptive qualitative approach using a library research method. The data consist of narrative excerpts, dialogues, and descriptions containing language styles in the novel 3726 MDPL by Nurwina Sari. The data source of this research is the novel text itself. Data were collected through careful reading and note-taking techniques involving identification and classification stages. The research instrument was the researcher herself, assisted by data recording sheets based on language style categories Nurgiyantoro. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that the novel 3726 MDPL contains various language styles, including comparative styles such as simile and metaphor, associative styles such as metonymy and synecdoche, repetition styles such as repetition, parallelism, and anaphora, as well as contrast styles such as hyperbole, irony, and paradox. The use of these language styles functions to strengthen meaning, build the emotional atmosphere of the characters, and enrich the aesthetic quality of the novel.